Cistanches Herba: A Neuropharmacology Review - Gu, Caimei; Yang, Xianying; Huang, Linfang (Frontiers in Pharmacology, 2016)
Cistanches Herba (family Orobanchaceae), commonly known as “desert ginseng” or Rou Cong Rong, is a global genus and commonly used for its neuroprotective, immunomodulatory, anti-oxidative, kidney impotence, laxative, anti-inflammatory, hepatoprotective, anti-bacterial, anti-viral, and anti-tumor effects in traditional herbal formulations in North Africa, Arabic, and Asian countries. The major bioactive compounds present in this plant is phenylethanoid glycosides. In recent years, there has been great important in scientific investigation of the neuropharmacological effects of the bioactive compounds. The in vitro and in vivo studies suggests these compounds demonstrate neuropharmacological activities against a wide range of complex nervous system diseases which occurs through different mechanisms include improving immunity function and kidney aging, anti-lipid peroxidation, scavenging free radical, inducing the activation of caspase-3 and caspase-8. This review aims to summaries the various neuropharmacological effects and mechanisms of Cistanches Herba extracts and related compounds, including its efficacy as a cure for Alzheimer’s disease (AD) and Parkinson’s disease (PD) with reference to the published literature. Which provides guidance for further research on the clinical application of Cistanches Herba.